Ginkgo biloba L. (Ginkgoaceae) Leaf Extract Medications From Different Providers Exhibit Differential Functional Effects on Mouse Frontal Cortex Neuronal Networks - Bader, Benjamin M.; Jügelt, Konstantin; Schultz, Luise; Schroeder, Olaf H.-U. (Frontiers in Pharmacology, 2018)
Background: Details of the extraction and purification procedure can have a profound impact on the composition of plant-derived extracts, and thus on their efficacy and safety. So far, studies with head-to-head comparison of the pharmacology of Ginkgo extracts rendered by different procedures have been rare. Objective: The objective of this study was to explore whether Ginkgo biloba leaf extract medications of various sources protect against amyloid beta toxicity on primary mouse cortex neurons growing on microelectrode arrays, and whether the effects differ between different Ginkgo extracts. Design: Our brain-on-chip platform integrates microelectrode array data recorded on neuronal tissue cultures from embryonic mouse cortex. Amyloid beta 42 (Aβ42) and various Ginkgo extract preparations were added to the networks in vitro before evaluation of electrophysiological parameters by multi-parametric analysis. A Multi-variate data analysis, called Effect Score, was designed to compare effects between different products. Results: The results show that Ginkgo extracts protected against Aβ42-induced electrophysiological alterations. Different Ginkgo extracts exhibited different effects. Of note, the reference Ginkgo biloba leaf medication Tebonin had the most pronounced rescuing effect. Conclusion: Here, we show for the first time a side-by-side analysis of a large number of Ginkgo medications in a relevant in vitro system modeling early functional effects induced by amyloid beta peptides on neuronal transmission and connectivity. Ginkgo biloba leaf extract from different manufactures exhibit differential functional effects in this neural network model. This in-depth analysis of functional phenotypes of neurons cultured on MEAs chips allows identifying optimal plant extract formulations protecting against toxin-induced functional effects in vitro.